The Facility Management Handbook. - Roper, Kathy O.; Payant, Richard P. (AMACOM, 2014)
Facility management (FM) is a multidisciplinary function requiring a deep knowledge of the entire business and physical planning cycle, including the buildings, infrastructure, and people. Technology systems, disaster recovery planning, zoning compliance, furnishings, recycling programs, grounds maintenance--it all falls under the facility management umbrella. The sheer scope of duties requires a far-reaching reference for staying abreast of the latest innovations and best practices. The Facility Management Handbook is that one essential book, packed with insightful overviews, case studies, an.